2021
DOI: 10.1021/acsapm.1c00580
|View full text |Cite
|
Sign up to set email alerts
|

Fire-Resistant Flexible Polyurethane Foams via Nature-Inspired Chitosan-Expandable Graphite Coatings

Abstract: The current methods used to impart flameretardant or fire-resistant properties to flexible polyurethane foams (PUFs) to meet fire safety requirements entail the use of halogenated phosphorus-based compounds. Whereas these are highly effective as flame retardants, the associated toxicity derived from halogens in the burning fumes are deadly. To address this problem, we herein present a facile and efficient method of fabricating highly fire-resistant flexible PUF using halogen-free nature-inspired coatings. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…The CH/AL alone coatings exhibited slightly higher pkHRR values than that of neat PUF (Figure S7), which is believed to be due to the flammability of the biopolymers. , Hence, the contribution of CH and AL to the flame retardancy of PUF is insufficient, except for acting as effective film-forming agents in the binding of PMC to the surface of the PUF. Usually, non-intumescent polymer-based FR coatings are not effective for PUF unless they are combined with an appropriate amount of particle-based, i.e., clay or carbon FRs. , Other LbL-deposited FRs on PUF, such as CH/GO and CH/ammonium polyphosphate, have also led to a decrease in pkHRR reduction upon increasing the number of bilayers. , Overall, the results showed that the PMC-filled coating significantly reduced pkHRR, one of the most important fire safety metrics that represents the point in a fire where the flame likely propagates to adjacent flammable materials. A lower pkHRR value implies a lower risk of spreading to neighboring flammable items, thereby providing more time for evacuation from a real fire incident .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The CH/AL alone coatings exhibited slightly higher pkHRR values than that of neat PUF (Figure S7), which is believed to be due to the flammability of the biopolymers. , Hence, the contribution of CH and AL to the flame retardancy of PUF is insufficient, except for acting as effective film-forming agents in the binding of PMC to the surface of the PUF. Usually, non-intumescent polymer-based FR coatings are not effective for PUF unless they are combined with an appropriate amount of particle-based, i.e., clay or carbon FRs. , Other LbL-deposited FRs on PUF, such as CH/GO and CH/ammonium polyphosphate, have also led to a decrease in pkHRR reduction upon increasing the number of bilayers. , Overall, the results showed that the PMC-filled coating significantly reduced pkHRR, one of the most important fire safety metrics that represents the point in a fire where the flame likely propagates to adjacent flammable materials. A lower pkHRR value implies a lower risk of spreading to neighboring flammable items, thereby providing more time for evacuation from a real fire incident .…”
Section: Resultsmentioning
confidence: 86%
“…Usually, non-intumescent polymer-based FR coatings are not effective for PUF unless they are combined with an appropriate amount of particlebased, i.e., clay or carbon FRs. 1,46 Other LbL-deposited FRs on PUF, such as CH/GO and CH/ammonium polyphosphate, have also led to a decrease in pkHRR reduction upon increasing the number of bilayers. 4,22 Overall, the results showed that the PMC-filled coating significantly reduced pkHRR, one of the most important fire safety metrics that represents the point in a fire where the flame likely propagates to adjacent flammable materials.…”
Section: Flame Retardant Propertiesmentioning
confidence: 99%
“…Notably, the hysteresis loops observed in liquid state were smaller and more stable than that in solid state due to the reduced buckling and decreased frictions in the sponge matrices in the liquid state, and also possibly minimizing mechanical damages across the composite structures, such as cracks. [ 37c,45 ]…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan, shown in Figure 13d, is a fibrous compound extracted from crustacean shells. Wong et al [114] coated FPUFs with chitosan and EG using single-step coating. In the cone calorimeter measurements, the combination of chitosan and EG in FPUFs significantly reduced the PHRR, THR, and TSR.…”
Section: Natural Renewable Resources As Flame-retardant Additivesmentioning
confidence: 99%